Newly discovered tetraploid Fagopyrum homotropicum in Tibet, China - Ding, Mengqi; Zhang, Kaixuan; Tang, Yu; Wang, Junzhen; Li, Faliang; Yang, Keli; Wen, Wen; Zhou, Meiliang (Phytotaxa, 2021)
A cryptic species of Fagopyrum (Polygonaceae), F. homotropicum, is described and illustrated from Mangkang county, Tibet, China. F. homotropicum was firstly discovered in the 90’s, being to be diploid and characterized being a self-pollinating taxon. Detailed information of F. homotropiucm was rarely reported. In this paper, we summarized the morphological and karyological characters of tetraploid form F. homotropiucm (2n=4x=32), it is self-pollinating, and morphology indistinguishable in comparison from the diploid form.